Relationship of job involvements on vocational school students’ job satisfactions in industrial training - Tarawe, Aminuddin Alidin (Academic Journal, 2013)
Industrial training is an important strategy to expose students to the real job situation so that they should be able to develop their job competency after completing their schooling. Industrial training program was known as the dual system program curriculum in vocational high schools. It was implemented for three to six months. This study examined the difference and relationship between job involvements towards job satisfactions in industrial training activities which were implemented for vocational school students. Data were collected from 300 vocational high school students using questionnaire. The selection of respondents was based on simple randomized sampling methods. The results of questionnaire were analyzed using descriptive analysis, one way ANOVA, and Person Correlation analysis with 99% level of reliability. Results showed that the level of students’ job involvements and job satisfactions were high. The study showed that there was no difference between students’ job involvements and job satisfactions with respect to the three groups, three months, four months and six months. The study also showed that there was a significant relationship between students’ job involvements and job satisfactions in industrial training.